EVALUASI PROGRAM PENUGASAN DOSEN DI SEKOLAH (PDS) FKIP UNIVERSITAS LAMPUNG MENGGUNAKAN MODEL CIPP - Neni Hasnunidah; Abdurrahman Abdurrahman; Een Yayah Haenilah; Hermi Yanzi; Sri Hastuti Noer (Universitas Lampung, 2022)
Lecturer Assignments in Schools or Penugasan Dosen di Sekolah (PDS) is one of the flagship programs for revitalizing TTIs based on partnerships with schools. The PDS program at FKIP Unila that has been implemented needs to be evaluated for its level of success. The purpose of this evaluation is to describe the level of success in implementing the PDS program at FKIP Unila as a whole in terms of context, input, process, and product. The program evaluation model uses the CIPP model (Context, Input, Process, Product). Data collection techniques were used in the form of observation, distributing questionnaires, and document analysis. Evaluation data were analyzed descriptively and qualitatively with stages, namely data reduction, data presentation, and conclusion. The evaluation results show that the PDS FKIP Unila program was successful in terms of context, input, process, and product. Success in terms of context is demonstrated by the legal basis for program implementation which is clear and has program objectives that are in line with the revitalization of the LPTKs by increasing the professionalism of teachers. Success in terms of input is demonstrated by instructors who are competent in their fields, professional organizing teams, program materials that are by the school curriculum, supporting facilities and infrastructure, and sufficient budget funds. Success in terms of the process includes the implementation of the activity plan according to the specified schedule, the performance of the organizers and instructors being optimal, the participants being able to participate in education and training actively and well, and evaluations are carried out thoroughly both for evaluation of participants, instructors, and organizers. Success in terms of product is obtaining output in the form of best practices in the form of reflective journals, videos, and learning media as well as articles published in international proceedings and reputable international journals. Based on the evaluation results, the implementation of the Unila FKIP PDS program was effective in providing solutions for increasing the professionalism of educators. AbstrakPenugasan Dosen di Sekolah (PDS) merupakan salah satu program unggulan revitaliasi LPTK berbasis kemitraan dengan sekolah. Program PDS di FKIP Unila yang telah dilaksanakan perlu dievaluasi tingkat keberhasilannya. Tujuan evaluasi ini adalah mendeskripsikan tingkat keberhasilan pelaksanaan program PDS di FKIP Unila secara menyeluruh dalam hal konteks, masukan, proses, dan produk. Model evaluasi program menggunakan model CIPP (Context, Input, Process, Product). Teknik pengumpulan data yang digunakan berupa observasi, penyebaran kuesioner, dan analisis dokumen. Data evaluasi dianalisis secara deskriptif kualitatif dengan tahapan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil evaluasi menunjukkan bahwa program PDS FKIP Unila berhasil dilihat dari segi konteks, masukan, proses, dan produk. Keberhasilan dari segi konteks ditunjukkan dari dasar hukum pelaksanaan program yang jelas dan memiliki tujuan program yang sesuai dengan revitalisasi LPTK dengan peningkatan profesionalitas guru. Keberhasilan dari segi masukan ditunjukkan dari instruktur yang kompeten dibidangnya, tim penyelenggara yang profesional, materi program yang sesuai dengan kurikulum sekolah, sarana dan prasarana yang mendukung serta dan anggaran dana yang mencukupi. Keberhasilan dari segi proses meliputi keterlaksanaan rencana kegiatan telah sesuai dengan jadwal yang ditentukan, kinerja penyelenggara dan instruktur sudah optimal, peserta mampu mengikuti pendidikan dan pelatihan dengan aktif dan baik, dan evaluasi dilakukan secara menyeluruh baik evaluasi peserta, instruktur maupun penyelenggara. Keberhasilan dari segi produk yaitu diperolehnya luaran berupa best practices dalam bentuk jurnal refleksi, video dan media pembelajaran serta artikel yang diterbitkan dalam prosiding internasional dan jurnal internasional bereputasi. Berdasarkan hasil evaluasi, maka pelaksanaan program PDS FKIP Unila efektif dalam memberikan solusi bagi peningkatan profesionalitas pendidik. DOI: https://doi.org/10.23960/rp/v2i2.hal.150-169